Mxene / Mg (OH) 2 catalyst for organic liquid hydrogen carrier as well as preparation method and application of Mxene / Mg (OH) 2 catalyst
By using Mxene/Mg(OH)2 catalyst in organic liquid hydrogen support, Mxene is uniformly distributed in Mg(OH)2 nanosheets, the existing catalyst cost and complex preparation problems are solved, and efficient and environmentally friendly hydrogen is achieved Storage and conversion effects.
Patent Information
- Application Number
- CN202411212509.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-03
AI Technical Summary
The existing organic liquid hydrogen support catalysts have problems such as high cost, complex preparation processes, environmental pollution and high catalytic activation energy, and it is difficult to achieve efficient and selective hydrogenation and dehydrogenation reactions.
Using Mxene/Mg(OH)2 catalyst, the catalyst is prepared by uniformly distributing Mxene in two-dimensional Mg(OH)2 nanosheets by ball milling, providing a low-cost and simple catalyst process suitable for organic liquid hydrogen support. hydrogenation and dehydrogenation reaction.
It has achieved a catalyst with high catalytic performance, low cost and environmental protection. After catalytic hydrogenation, the hydrogen capacity retention rate of the organic liquid hydrogen support is high, suitable for industrial production, and the reaction conditions are optimized to improve the hydrogen conversion rate.
Smart Images

Figure CN119236982A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic liquid hydrogen carriers, and in particular relates to an environmentally friendly, low-cost Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier, and a preparation method and application thereof. Background Art
[0002] Energy is an indispensable basic element supporting the development of human society. In daily life, fossil fuels are the most widely used form of energy. Since humans began to use fossil fuels on a large scale, they have dominated the global energy supply and still dominate energy consumption. However, over-reliance on fossil fuels has also brought a series of negative effects, including the contradiction between the growing energy demand and the depletion of traditional energy resources, as well as the resulting environmental pollution problems. Against this background, a series of sustainable clean energy sources are gradually attracting people's attention. Hydrogen, as a green and efficient secondary energy source, is regarded as an ideal renewable energy carrier. However, the practical application of hydrogen energy also requires breakthroughs in technologies such as low-cost hydrogen production, efficient hydrogen conversion, and safe and compact hydrogen storage.
[0003] The currently dominant conventional gas or liquid hydrogen storage methods require fairly high operating pressures, such as high-pressure gas cylinders or liquid hydrogen storage tanks. Liquid Organic Hydrogen Carriers (LOHCs) are a class of organic liquids that can store hydrogen in the form of chemical bonds, and show great potential in efficient and stable hydrogen storage and transportation. Within the standard industrial pressure range, the volumetric hydrogen storage density of LOHCs is significantly higher than that of gaseous hydrogen storage carriers; compared with solid hydrogen storage carriers, a significant advantage of LOHCs is their compatibility with existing chemical fuel storage and transportation systems. Therefore, LOHC technology operating at ambient pressure provides a denser, safer, and more cost-effective hydrogen storage solution that can achieve safe and economical large-scale hydrogen transportation and long-term hydrogen storage.
[0004] Although LOHC technology exhibits extremely practical hydrogen storage properties and can achieve economical, safe and easy-to-manage operating procedures, it still faces a series of challenges, including the complexity and diversity of the reaction process, high activation energy requirements, difficult to accurately control reaction selectivity, and incomplete dehydrogenation. Therefore, the problem of how to make the catalyst efficiently and selectively carry out hydrogenation and dehydrogenation reactions has not yet been solved. In addition, due to the large amount of precious metal catalysts used in LOHC technology, the cost is relatively high.
[0005] LOHC catalysts are the key components of LOHC technology in the hydrogen storage process. Efficient and long-life catalysts can not only effectively reduce costs, but also reduce the temperature required for the reaction, while increasing the reaction rate and conversion rate. Common methods for preparing LOHC catalysts include hydrothermal method, sol-gel method, sputtering method, laser etching method, thermal evaporation method and thermal chemical vapor deposition method. However, the catalysts prepared by these methods have some limitations, such as high production costs, low yields, complex preparation processes and potential environmental pollution problems. These problems seriously restrict the practical application of LOHC catalysts. Therefore, the development of low-cost and simple methods to obtain LOHC catalysts with specific structures is still of great significance in promoting their practical applications.
[0006] Patent application CN116726970A discloses a sulfur-nitrogen doped MXene hydrogen storage material catalyst, a hydrogen storage material containing the catalyst and a preparation method, which belongs to the field of hydrogen storage technology. The hydrogen storage material catalyst is sulfur-nitrogen doped Nb2CT x , the hydrogen storage catalyst and magnesium hydride are ball-milled to obtain a composite hydrogen storage material. The catalyst has an excellent catalytic effect on the hydrogen absorption and desorption process of magnesium hydride. The composite hydrogen storage material prepared with the catalyst and magnesium hydride can achieve 5.32wt.% hydrogen release within 5 minutes at 275°C during the hydrogen desorption kinetics test, and can achieve 5.08wt.% hydrogen absorption within 2 minutes at 150°C during the hydrogen absorption kinetics test. In addition, the initial hydrogen desorption temperature of the composite hydrogen storage material is reduced by 105.48°C compared with pure magnesium hydride. However, the sulfur-nitrogen-doped MXene hydrogen storage material catalyst is aimed at improving the hydrogen absorption and desorption performance of magnesium hydride solid hydrogen storage materials, and the cost is high. Patent application CN117085713A discloses a MXene hydrogen storage material catalyst, a hydrogen storage material containing the catalyst and a preparation method, which belongs to the field of hydrogen storage technology. The catalyst has higher catalytic activity and has great advantages in improving the performance of magnesium-based hydrogen storage. After compounding it with MgH2, the composite hydrogen storage material releases 6.10wt.% of hydrogen within 4 minutes at 280°C, and absorbs 5.26wt.% of hydrogen within 60 seconds at 100°C. In addition, after 50 cycles of hydrogen absorption and desorption, the composite hydrogen storage material can still maintain a hydrogen storage capacity of more than 4.8wt.%. However, the hydrogen storage material catalyst cannot be directly used in the field of liquid organic hydrogen storage materials, and must be loaded on a carrier before use, which is a complicated process. Summary of the invention
[0007] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier and a preparation method and application thereof. The catalyst has a large specific surface area and good catalytic performance. The hydrogen capacity retention rate of the organic liquid hydrogen carrier after catalytic hydrogenation is high.
[0008] The purpose of the present invention can be achieved by the following technical solutions:
[0009] The present invention provides a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier. The catalyst comprises an active component and a matrix. The active component is Mxene, and the matrix is Mg(OH)2. The mass ratio of the Mg source to the Mxene is 0.5:1-50:1.
[0010] Furthermore, the mass ratio of the Mg source to Mxene is 4:1-50:1.
[0011] Furthermore, the Mxene is Ti3C2T x , T is O 2- Any of the OH-, or F- functional groups.
[0012] Furthermore, the Mxene is uniformly distributed in Mg(OH)2, and the Mg(OH)2 is a two-dimensional Mg(OH)2 nanosheet, and the width of the Mg(OH)2 nanosheet is 300-700nm and the thickness is 20-60nm.
[0013] In another aspect, the present invention provides a method for preparing the above-mentioned Mxene / Mg(OH)2 catalyst for organic liquid hydrogen carrier, comprising the following steps:
[0014] S1, mixing Mg-based solid materials with Mxene;
[0015] S2, placing the mixture of the Mg-based solid material and Mxene in a ball mill for ball milling to obtain a Mxene / Mg-based solid material composite material;
[0016] S3, hydrolyzing the Mxene / Mg-based solid material composite material, filtering the hydrolyzate, and drying it to obtain the Mxene / Mg(OH)2 catalyst.
[0017] Furthermore, in step S1, the Mg-based solid material is one of Mg powder or MgH2, and the mass ratio of the Mg-based solid material to Mxene is 4:1-50:1.
[0018] Furthermore, in step S2, the ball milling conditions are: ball milling is carried out under an inert gas atmosphere, the ball-to-material ratio is 5:1-50:1, the ball milling speed is 300-500 rpm, and the ball milling time is 5-50 hours.
[0019] Furthermore, in step S3, the drying is specifically performed at a drying temperature of 40-100° C. and a drying time of 10-24 hours.
[0020] In a third aspect, the present invention also provides an application of the above-mentioned Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier in an organic liquid hydrogen carrier. The organic liquid hydrogen carrier and the above-mentioned catalyst are added to a high-temperature and high-pressure reactor at a mass ratio of 10:1, and the catalytic hydrogenation and dehydrogenation of the organic liquid hydrogen carrier are carried out at a certain temperature and pressure.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The present invention provides an environmentally friendly Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier. In the catalyst, Mxene is uniformly distributed in a Mg(OH)2 matrix of a two-dimensional nanosheet structure, wherein the thickness of the Mg(OH)2 nanosheet is about 40 nm and the width is about 500 nm. The Mg(OH)2 nanosheet structure is beneficial to the dehydrogenation of the organic liquid hydrogen carrier, and the interaction between Mxene and the carrier is beneficial to electron conduction.
[0023] (2) The Mxene / Mg(OH)2 catalyst provided by the present invention has high purity, uniform morphology, large specific surface area and good catalytic performance. The organic liquid hydrogen carrier and the Mxene / Mg(OH)2 catalyst with a mass ratio of 10:1 were added to a high temperature and high pressure reactor. After reacting at 160°C and 6MPa for 18 hours, the conversion rate of ethylcarbazole was 99.2%, and 5.72wt.% of hydrogen was released. It has good application and industrialization prospects in the field of organic liquid hydrogen carriers.
[0024] (3) The organic liquid hydrogen carrier catalyst and the preparation method thereof provided by the present invention have readily available raw materials, simple preparation process, convenient operation, and can be used for large-scale industrial production. No toxic substances are used in the reaction, the reaction impurities are very few, and a high-purity product is easily obtained without pollution to the environment.
[0025] (4) The organic liquid hydrogen carrier catalyst and preparation method provided by the present invention is a novel, simple, efficient, inexpensive, additive-free green synthesis scheme, which effectively solves the difficult-to-overcome agglomeration and adhesion problem in the preparation of Mg(OH)2 nanosheets, improves the dispersion performance of nano Mg(OH)2, and ultimately improves the catalytic performance of the nanocomposite material Mxene / Mg(OH)2. Compared with the traditional chemical reaction to prepare Mg(OH)2, no additional chemical reagents are required, which is energy-saving and environmentally friendly, and greatly gives play to my country's mineral resource advantages. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a low-magnification FESEM image of the Ti3C2 / Mg(OH)2 catalyst;
[0027] Figure 2This is a high-magnification FESEM image of the Ti3C2 / Mg(OH)2 catalyst;
[0028] Figure 3 XRD pattern of Ti3C2 / Mg(OH)2 catalyst;
[0029] Figure 4 This is the EDS spectrum of Ti3C2 / Mg(OH)2 catalyst;
[0030] Figure 5 This is the EDS spectrum test result of Ti3C2 / Mg(OH)2 catalyst;
[0031] Figure 6 This is the test curve of Ti3C2 / Mg(OH)2 catalyst for ethylcarbazole (NEC) hydrogenation performance;
[0032] Figure 7 This is the XRD pattern of Ti3C2 / MgH2 composite material. DETAILED DESCRIPTION
[0033] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0034] Unless otherwise specified, the reagents, methods, instruments and equipment used in the present invention are conventional reagents, methods, instruments and equipment in the art. Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0035] For example, MgH2 used in the present invention was purchased from Aladdin Chemical Reagent Platform, Mxene was purchased from Xianfeng Nano (Article No.: 102475), and ethylcarbazole (NEC) was purchased from Adamas.
[0036] The present invention provides a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier, the catalyst comprising an active component and a matrix, the active component being Mxene, the matrix being Mg(OH)2, wherein the mass ratio of the Mg source to the Mxene is 0.5:1-50:1, preferably, the mass ratio of the Mg source to the Mxene is 4:1-50:1. The Mxene is Ti3C2T x , T is O 2- OH - , or F - Any one of the functional groups, Mxene is uniformly distributed in Mg(OH)2; Mg(OH)2 is a two-dimensional Mg(OH)2 nanosheet, the width of the Mg(OH)2 nanosheet is 300-700nm, and the thickness is 20-60nm.
[0037] The preparation method of the above catalyst comprises the following steps:
[0038] S1, mixing Mg-based solid materials with Mxene;
[0039] S2, placing the mixture of the Mg-based solid material and Mxene in a ball mill for ball milling to obtain a Mxene / Mg-based solid material composite material;
[0040] S3, hydrolyzing the Mxene / Mg-based solid material composite material, filtering the hydrolyzate, and drying it to obtain the Mxene / Mg(OH)2 catalyst.
[0041] In some specific embodiments, in step S1, the Mg-based solid material is one of Mg powder or MgH2, and the mass ratio of the Mg-based solid material to Mxene is 4:1-50:1.
[0042] In some specific embodiments, in step S2, the ball milling conditions are: ball milling is carried out under an inert gas atmosphere, the ball-to-material ratio is 5:1-50:1, the ball milling speed is 300-500 rpm, and the ball milling time is 5-50 hours.
[0043] In some specific embodiments, in step S3, the drying is specifically performed at a drying temperature of 40-100° C. and a drying time of 10-24 h.
[0044] The obtained catalyst can be used for an organic liquid hydrogen carrier. The organic liquid hydrogen carrier and the prepared catalyst are added into a high temperature and high pressure reactor at a mass ratio of 10:1, and the catalytic hydrogenation and dehydrogenation of the organic liquid hydrogen carrier are carried out at a certain temperature and pressure.
[0045] Example 1
[0046] The specific steps of this embodiment are as follows:
[0047] MgH2 and Mxene with a mass ratio of 19:1 were mechanically ground, and then a MgH2-5wt% Ti3C2 composite material was prepared by ball milling. The ball milling process was carried out on a ball mill (FRITSCH 06.2000 / 04350) under an argon atmosphere for 10 hours. The ball-to-material ratio during ball milling was 30:1 and the ball milling speed was 400rpm. The ground MgH2-5wt% Ti3C2-based composite material was hydrolyzed, and the hydrolyzate was obtained by filtering the hydrolyzed solution and dried in a blast oven at 60°C for 20 hours to finally obtain a Ti3C2 / Mg(OH)2 composite catalyst. Then, the organic liquid hydrogen carrier ethylcarbazole (NEC) and the Ti3C2 / Mg(OH)2 composite catalyst sample were added into a high temperature and high pressure reactor in a mass ratio of 10:1, and the catalytic hydrogenation and dehydrogenation chemical performance tests of the organic liquid hydrogen carrier ethylcarbazole (NEC) were carried out. The test conditions were: after 18 hours of reaction at 160°C and 6MPa, the conversion rate of ethylcarbazole was 99.2%, and 5.72wt.% of hydrogen was released.
[0048] like Figure 1 As shown in Figure 2, the low magnification FESEM image of the Ti3C2 / Mg(OH)2 catalyst shows that Ti3C2 is uniformly distributed in Mg(OH)2 in the catalyst. Figure 2 As shown, this is a high-magnification FESEM image of the Ti3C2 / Mg(OH)2 catalyst. It can be found that the prepared two-dimensional Mg(OH)2 matrix is distributed in a petal shape with a width of about 400nm and a thickness of about 50nm.
[0049] Figure 3 is the XRD pattern of Ti3C2 / Mg(OH)2 catalyst. Figure 7 is the XRD pattern of MgH2-5wt%Ti3C2 sample before hydrolysis, such as Figure 7 As shown in the figure, it is found that the sample before hydrolysis has a MgH2 characteristic peak; and through the detection spectrum after hydrolysis, it can be seen that the detection spectrum of the hydrolysis product is almost all composed of clear Mg(OH)2 characteristic peaks ( Figure 3 ), the characteristic diffraction peak of MgH2 can no longer be detected.
[0050] Figure 4 This is the EDS energy spectrum of Ti3C2 / Mg(OH)2 catalyst. According to the element distribution results of the energy spectrum, it is found that Ti3C2 / Mg(OH)2 catalyst contains Mg, C, Ti, O and other elements, and the corresponding element distribution is relatively uniform. Figure 5 The EDS energy spectrum test results of the Ti3C2 / Mg(OH)2 catalyst show that the Mg content in the Ti3C2 / Mg(OH)2 catalyst is 48.12wt%, the C content is 5.85wt%, the Ti content is 1.14wt%, and the O content is 44.89wt%.
[0051] Figure 6 This is the test curve of the Ti3C2 / Mg(OH)2 catalyst for the hydrogenation performance of ethylcarbazole (NEC). The results show that the Ti3C2 / Mg(OH)2 composite catalytic chemical performance is good. After reacting at 160°C and 6MPa for 18 hours, the ethylcarbazole conversion rate is 99.2%, and 5.72wt.% of hydrogen is released.
[0052] Example 2
[0053] The Mg powder and Mxene with a mass ratio of 50:1 were mechanically ground, and then the Mg-1.96wt%Ti3C2 composite material was prepared by ball milling. The ball milling process was carried out on a ball mill (FRITSCH 06.2000 / 04350) under an argon atmosphere for 5 hours. The ball-to-material ratio during ball milling was 20:1 and the ball milling speed was 400rpm. The ground Mg-1.96wt%Ti3C2-based composite material was hydrolyzed, and the hydrolyzate was obtained by filtering the hydrolyzed solution and dried in a blast oven at 50°C for 10 hours to finally obtain a Ti3C2 / Mg(OH)2 composite catalyst. Then, ethylcarbazole (NEC) and Ti3C2 / Mg(OH)2 composite catalyst samples were added into a high-temperature and high-pressure reactor in a mass ratio of 10:1. After reacting for 20 hours at 160°C and 7MPa, the catalytic hydrogenation and dehydrogenation chemical properties of the organic liquid hydrogen carrier ethylcarbazole (NEC) were tested. The conversion rate of ethylcarbazole was 97.7%, and 5.67% of hydrogen was released.
[0054] Example 3
[0055] The Mg powder and Mxene with a mass ratio of 0.5:1 were mechanically ground, and then the Mg-66.67wt%Ti3C2 composite material was prepared by ball milling. The ball milling process was carried out on a ball mill (FRITSCH 06.2000 / 04350) under an argon atmosphere for 10 hours. The ball-to-material ratio during ball milling was 40:1 and the ball milling speed was 500rpm. The ground Mg-66.67wt%Ti3C2-based composite material was hydrolyzed, and the hydrolyzate was obtained by filtering the hydrolyzed solution and dried in a blast oven at 70°C for 20 hours to finally obtain a Ti3C2 / Mg(OH)2 composite catalyst. Finally, ethylcarbazole (NEC) and Ti3C2 / Mg(OH)2 composite catalyst samples were added into a high-temperature and high-pressure reactor in a mass ratio of 10:1. After reacting for 20 hours at 170°C and 7MPa, the catalytic hydrogenation and dehydrogenation chemical properties of the organic liquid hydrogen carrier ethylcarbazole (NEC) were tested. The conversion rate of ethylcarbazole was 96.8%, and 5.63% of hydrogen was released.
[0056] Comparative Example 1
[0057] The Pd / Mg(OH)2 prepared in the open document A highly active Pd clusters hosted by magnesium hydroxide nanosheets promoting hydrogen storage, Applied Catalysis B: Environmental (IF=24.319), Volume 333, 15 September 2023, 122793 was used as a comparative example.
[0058] The reaction parameters and reaction results of the above Examples 1-3 and Comparative Example 1 are shown in Table 1:
[0059] Table 1 Reaction parameters and reaction results of Examples 1-3 and Comparative Example 1
[0060]
[0061]
[0062] Public document A highly active Pd clusters hosted by magnesium hydroxide nanosheets promoting hydrogen storage, Applied Catalysis B: Environmental (IF = 24.319) provides a LOHC catalyst Pd / Mg (OH) 2, but the process conditions are complicated, the noble metal Pd is used, and the cost is also very high. The Mxene / Mg (OH) 2 catalyst material obtained by hydrolysis of the present invention is cheap, low in cost, and the catalytic performance is comparable to the Pd / Mg (OH) 2 catalyst in the document.
[0063] It can be seen from the above embodiments and comparative examples that the Mxene / Mg(OH)2 catalyst prepared by the preparation method of the present invention has easy-to-obtain raw materials, a simple preparation process, convenient operation, good catalytic performance, and has good application and industrialization prospects in the field of organic liquid hydrogen carriers.
[0064] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier, characterized in that: The catalyst comprises an active component and a matrix, wherein the active component is Mxene and the matrix is Mg(OH)2; wherein the mass ratio of the Mg source to the Mxene is 0.5:1-50:
1.
2. The Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 1, characterized in that: The mass ratio of the Mg source to Mxene is 4:1-50:
1.
3. The Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 1, characterized in that: The Mxene is Ti3C2T x , T is O 2- Any of the OH-, or F- functional groups.
4. The Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 1, characterized in that: The Mxene is uniformly distributed in Mg(OH)2, and the Mg(OH)2 is a two-dimensional Mg(OH)2 nanosheet.
5. The Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 4, characterized in that: The width of the Mg(OH)2 nanosheet is 300-700nm and the thickness is 20-60nm.
6. A method for preparing the Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier as claimed in any one of claims 1 to 5, characterized in that: The steps include: S1, mixing Mg-based solid materials with Mxene; S2, placing the mixture of the Mg-based solid material and Mxene in a ball mill for ball milling to obtain a Mxene / Mg-based solid material composite material; S3, hydrolyzing the Mxene / Mg-based solid material composite material, filtering the hydrolyzate, and drying it to obtain the Mxene / Mg(OH)2 catalyst.
7. The method for preparing a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 6, characterized in that: In step S1, the Mg-based solid material is one of Mg powder and MgH2, and the mass ratio of the Mg-based solid material to Mxene is 4:1-50:
1.
8. The method for preparing a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 6, characterized in that: In step S2, the ball milling conditions are: ball milling is carried out under an inert gas atmosphere, the ball milling ball-to-material ratio is 5:1-50:1, the ball milling speed is 300-500 rpm, and the ball milling time is 5-50 hours.
9. The method for preparing a Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier according to claim 6, characterized in that: In step S3, the drying conditions are: drying temperature 40-100° C., and drying time 10-24 h.
10. Use of the Mxene / Mg(OH)2 catalyst for an organic liquid hydrogen carrier as claimed in any one of claims 1 to 5 in an organic liquid hydrogen carrier.
Citation Information
Patent Citations
Sulfur-nitrogen doped MXene hydrogen storage material catalyst, hydrogen storage material containing catalyst and preparation method
CN116726970A
MXene hydrogen storage material catalyst, hydrogen storage material containing catalyst and preparation method
CN117085713A
